Influence of Motor Skill Training on Performance of Dressing as an Activity of Daily Living by Pupils with Cerebral Palsy; a Case of a Special School in Kisimu County, Kenya - Odhiambo, Janet Auma (JOOUST, 2016)
Cerebral palsy is a condition that has been in existence for a long time and there is no society that is exempted from having children with cerebral palsy. The prevalence of cerebral palsy is rising and Kenya just like the rest of the world is experiencing the increase. It has been reported that out of every 1000 newborn children in Kenya, 2% develop cerebral palsy. Children with cerebral palsy have motor impairments such as paralysis, weakness or incoordination that hinder them from performing the Activities of Daily Living. The purpose of this study was to find out the influence of motor skills training on the performance of dressing as an Activity of Daily Living by pupils with cerebral palsy. The study objectives were to find out the effectiveness of motor skills training as an intervention in the performance of dressing as an activity of daily living by pupils with cerebral palsy, to establish the factors influencing effectiveness of motor skill training for the performance of dressing as an activity of daily living by pupils with cerebral palsy, to find out the effectiveness of training on the fine and gross motor muscles for the performance of dressing as an activity of daily living and finally to establish the support services and institutional support systems available for pupils with cerebral palsy and their parents for the performance of Activities of Daily Living. The study was guided by the conscious competence theory. The study adopted a sequential explanatory design within a mixed methods • approach. The study population was 14 pupils with cerebral palsy at one Special School for the physically handicapped, 28 parents, 2 physiotherapists and 23 teachers. The sample size wasl2 pupils with cerebral palsy selected through purposive sampling, 3 teachers selected through saturated sampling technique, 2 physiotherapists and 8 parents of pupils with cerebral palsy selected through convinience sampling. Instruments for data collection were observations with the use of observational checklists, interview schedules for parents, teachers and physiotherapists, document analysis and Focus Group Discussion with the parents. Quantitative data was analyzed using descriptive and inferential statistics such as Wilcoxon Signed Rank Test, Mann-Whitney U Test and Kruskal-Wallis Tests to test the analysis.Qualitative data was analyzed using thematic framework. Validity of the instruments used was ensured by expert judgement of the university lecturers, while the reliability was ensured by the internal consistency and a reliability coefficient of 0.82 was reported. The findings of the study were; After motor skill training there were improvements on motor skill functioning among pupils who were in the experimental group while those in the control group had no improvements, the main factor that influenced the pupils ability to learn both the fine and gross motor skills was the severity of their disability and not their gender or age. The available support services and institutional systems available for pupils with cerebral palsy included the assistance from their teachers, teacher-aids, house mothers, roommates, and social workers. While at home the pupils with cerebral palsy get assistance from their mothers and siblings. The study recommended that the Ministry of Health should post physiotherapists and occupational therapists in learning institutions for the physically challenged to train teachers on how to give motor skills training to enable the pupils with cerebral palsy to function independently.